2012
DOI: 10.1007/s00216-012-6320-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of dl-lactic acid and dl-3-hydroxybutyric acid enantiomers in saliva of diabetes mellitus patients by high-throughput LC–ESI-MS/MS

Abstract: A simultaneous determination method for the enantiomers of chiral carboxylic acids by the combination of ultraperformance liquid chromatography and mass spectrometry (UPLC-MS/MS) has been developed. (S)(+)-1-(2-Pyrrolidinylmethyl)-pyrrolidine (S-PMP) was used as the derivatization reagent for the high-throughput determination of biological chiral carboxylic acids, i.e., lactic acid (LA) and 3-hydroxybutyric acid (HA). The S-PMP efficiently reacted with the carboxylic acids under mild conditions at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 41 publications
1
34
0
2
Order By: Relevance
“…The results reveal that both the D-and L-LA levels in the plasma of T2DM mice were significantly (P < 0.05) higher than those of normal mice ( Figure 4A and B), which is consistent with the literature [30,31]. There are other studies that have reported that the L-LA levels increased slightly without significance [32,33]. Significant increases of D-LA were reported in all studies involving the LA enantiomers and T2DM [4][5][6][29][30][31][32], suggesting that D-LA may serve as an indicator for T2DM.…”
Section: Determination Of D-and L-la and Dand L-2hg In T2dm Mouse Plsupporting
confidence: 90%
“…The results reveal that both the D-and L-LA levels in the plasma of T2DM mice were significantly (P < 0.05) higher than those of normal mice ( Figure 4A and B), which is consistent with the literature [30,31]. There are other studies that have reported that the L-LA levels increased slightly without significance [32,33]. Significant increases of D-LA were reported in all studies involving the LA enantiomers and T2DM [4][5][6][29][30][31][32], suggesting that D-LA may serve as an indicator for T2DM.…”
Section: Determination Of D-and L-la and Dand L-2hg In T2dm Mouse Plsupporting
confidence: 90%
“…7B), respectively. [27], and the %D-LA was 10.3%. The ratio was found to be 5.0% in our experiments.…”
Section: Clinical Applicationsmentioning
confidence: 90%
“…However, it was presumably caused by the differences between individuals or by various bacteria in the saliva. However, our 2D-HPLC method for measuring D/L-3HB has better chromatographic separation efficiency than the LC-MS/MS method used by Tsutsui et al [27].…”
Section: Clinical Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, previously reported analytical methods suffer from several innate shortcomings, including the use of time-consuming gas chromatography coupled to mass spectrometry (GC/MS), [17] the need for complex derivatization procedures with expensive reagents, [18] or, in some cases, using derivatization reagents that are potentially explosive. [19] Furthermore, more rapid approaches reported in the past have only demonstrated the detection of a limited number (1 to 5) of AHAs, [13,[20][21][22] or have not used more specific mass spectrometric detection. [23] Ideally, an improved AHA analytical method should be able to detect and quantitate a larger suite of AHAs in a single chromatographic run without derivatization.…”
mentioning
confidence: 99%